APPLICABILITY OF DIFFUSION OF INNOVATION THEORY IN ORGANIC AGRICULTURE - Tomaš Simin, Mirela; Janković, Dejan (Economics of Agriculture, 2014)
The authors discuss the possibility of applying the theory of diffusion of innovations in the concept of organic farming. Agricultural and food sector has been exposed to significant changes over the past two centuries. That was very significant for the theory of diffusion of innovations that sought to better understand the process of knowledge transfer and adoption of innovations. Organic farming has developed as a response to the environmental and other problems of conventional agriculture. Also, it is a reaction to some issues regarding rural development. By introducing the theory of diffusion of innovation, the aim of the paper is to take into the consideration the possibility of its application to the organic system analysis. By that, we wish to take into account all the specifics which enable to observe the system of organic farming as an innovation itself. The authors conclude that the theory of diffusion of innovations can be used in the research of organic farming systems, with the respect of all characteristics and particularities of organic farming.